NARASI PEREMPUAN DALAM FEMVERTISING SHOPEE “DARI KAMI #UNTUKPEREMPUAN” - Raflykasari Suci Sugesti; Fajar Junaedi (SOURCE : Jurnal Ilmu Komunikasi, 2026)
This article explains how the Shopee ad "Dari Kami #UntukPerempuan" uses femvertising to highlight the issue of women's rights and even encourage them to participate in e-commerce. The purpose of this study is to determine if the gender-based kesetaraan in the aforementioned campaign has been used as an autistic dukungan or as a komodifikasi strategy. Using a deskriptif kualitatif method and narrative analysis using a modified Todorov structure, the study examines representation in three primary narratives: sexual harassment, body shaming, and gender prejudice in the workplace. The analysis's findings indicate that the journey from ketidakadilan to dukungan and pemulihan is facilitated by iklan, which also highlights the importance of social solidarity as a means of promoting women's rights. However, research also indicates that there is a potential for conflict if feministic values are undermined in the pursuit of commercial goals. This article contributes to the conversation on the differences between the use of symbols and marketing strategies in femvertising.